Microsoft Power BI cookbook : creating business intelligence solutions of analytical data models, reports, and dashboards - Powell, Brett (Packt Publishing, 2017)
Get more out of Microsoft Power BI turning your data into actionable insights About This Book From connecting to your data sources to developing and deploying immersive, mobile-ready dashboards and visualizations, this book covers it all Over 90 hands-on, technical recipes, tips, and use cases from across the Power BI platform including the Power BI Service and Mobile Applications Proven development techniques and guidance for implementing custom solutions with DAX and M languages Who This Book Is For This book is for BI professionals who wish to enhance their knowledge of Power BI beyond and to enhance the value of the Power BI solutions they deliver to business users. Those who are looking at quick solutions to common problems while using Power BI will also find this book to be a very useful resource .Some experience with Power BI will be useful. What You Will Learn Cleanse, stage, and integrate your data sources with Power BI Abstract data complexities and provide users with intuitive, self-service BI capabilities Build business logic and analysis into your solutions via the DAX programming language and dynamic, dashboard-ready calculations Take advantage of the analytics and predictive capabilities of Power BI Make your solutions more dynamic and user specific and/or defined including use cases of parameters, functions, and row level security Understand the differences and implications of DirectQuery, Live Connections, and Import-Mode Power BI datasets and how to deploy content to the Power BI Service and schedule refreshes Integrate other Microsoft data tools such as Excel and SQL Server Reporting Services into your Power BI solution In Detail Microsoft Power BI is a business intelligence and analytics platform consisting of applications and services designed to provide coherent, visual and interactive insights of data. This book will provide thorough, technical examples of using all primary Power BI tools and features as well as demonstrate high impact end-to-end solutions that leverage and integrate these technologies and services. Get familiar with Power BI development tools and services, go deep into the data connectivity and transformation, modeling, visualization and analytical capabilities of Power BI, and see Power BI's functional programming languages of DAX and M come alive to deliver powerful solutions to address common, challenging scenarios in business intelligence. This book will excite and empower you to get more out of Pow ...
Keywords: Business intelligence -- Computer programs.; Information visualization -- Computer programs.; Business -- Data processing.; Visual analytics.; Management -- Data processing.; elektronické knihy; electronic books